2012
DOI: 10.33225/jbse/12.11.347
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between University Students’ Organic Chemistry Anxiety, Chemistry Attitudes, and Self-Efficacy: A Structural Equation Model

Abstract: The purpose of this study is to examine the relationships between organic chemistry anxiety, chemistry attitudes, and self-efficacy. Participants were 368 sophomore undergraduate students. In this study, the Organic Chemistry Anxiety Scale (O-CAS), the Chemistry Attitudes Scale, and the Self-efficacy Scale were used. Pearson correlation coefficient and structural equation modeling was utilized to determine the relationships between organic chemistry anxiety, chemistry attitudes, and self-efficacy. In correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In the CURE module, students learned the green chemistry synthetic method, modern analytical instruments, and data analysis method, which can build up their positive self-efficacy or increase their self-efficacy and prepare them for their future careers in industry or future studies in graduate school. The positive self-efficacy results in this study were similar to the findings in previous CURE studies and in general and organic chemistry laboratory courses. , As higher self-efficacy is associated with higher academic achievement, more positive perception of the course and attitude, less anxiety, and higher critical thinking, the positive self-efficacy is likely to promote these outcomes which are indicators of student success in chemistry. There was a significant sex main effect on self-efficacy and females scored significantly lower than males before the CURE module, suggesting there was a sex equity gap in students’ confidence in research skills.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the CURE module, students learned the green chemistry synthetic method, modern analytical instruments, and data analysis method, which can build up their positive self-efficacy or increase their self-efficacy and prepare them for their future careers in industry or future studies in graduate school. The positive self-efficacy results in this study were similar to the findings in previous CURE studies and in general and organic chemistry laboratory courses. , As higher self-efficacy is associated with higher academic achievement, more positive perception of the course and attitude, less anxiety, and higher critical thinking, the positive self-efficacy is likely to promote these outcomes which are indicators of student success in chemistry. There was a significant sex main effect on self-efficacy and females scored significantly lower than males before the CURE module, suggesting there was a sex equity gap in students’ confidence in research skills.…”
Section: Discussionsupporting
confidence: 66%
“…Meta-analyses and reviews showed that self-efficacy can predict student academic performance . In the chemistry context, literature has reported self-efficacy is a predictor of student academic outcomes, such as academic achievement, perception of the chemistry course, attitude, anxiety, and critical thinking . The consideration of student self-efficacy was central to the URC programs.…”
Section: Introductionmentioning
confidence: 99%